Sustainable Development Within the Context of International Environmental Politics & Non-State Actors & The Limitations by Neo-Liberalism Against Climate Change - Gümüşfiliz, Nadire Burcu (Advances in Social Sciences Research Journal, 2023)
Sustainable development has become a crucial concept that includes a wide range of issues in many different areas. It highlights the aspects of environmental, political and social dimensions of development. Within this perspective, this paper analyses the significance of international environmental issues by taking into consideration the effects of international environmental politics based on the claim of assuring and promoting sustainable development. This paper also aims to shed light on the role and the significance of NGOs in global politics which mostly take part in global environmental governance against the neoliberal state policies. In this sense, it discusses that the role of NGOs come to the forefront which play a part in international politics that are supposed to make contributions to international environmental politics. Furthermore, this study discusses using resources as brwell as to prevent and overcome climate change in a sustainable manner which is driven by international environmental politics based on NGOs by also considering the meaning of NeoLiberalism and its impacts on international environment in a critical perspective with regard to sustainable development. Thereby, understanding the impacts of global issues as climate change is an urgent and a required task in the sense that they play a major role in the case of understanding the importance of global environmental politics and the role of NGOs and international agreements with regard to environmentally sustainable development. More precisely, this study deals with the question of how global environmental issues and problems arise basically with the neo-liberal policies and important role of NGOs as well as international institutions in order to contribute to sustainable development in relation to international environmental politics. This paper examines the role of NGOs and the importance of international institutions in coping with global environmental problems with respect to international environmental politics based on qualitative descriptive research./p